2018
DOI: 10.1002/er.4165
|View full text |Cite
|
Sign up to set email alerts
|

An improved model for predicting the performance of parabolic trough solar collectors

Abstract: Summary An improved solar parabolic trough collector model has been developed in this study, to overcome the weakness of the previous published studies in predicting accurate performance, at higher operating temperatures. To check the accuracy of the proposed model, both on‐sun and off‐sun tests have been considered. The on‐sun tests are aimed to check the potential of the model for predicting the thermal efficiency while off‐sun tests are for heat losses. The results have indicated that the efficiency uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Similarly, Odeh et al (1998) used direct steam generation over an indirect steam generation in a PTC system and the system performance was calculated with the help of an equation. Agagna et al (2018) predicted the accuracy and performance of the system by comparing their PTC model with an existing system while the results reported about 0.5% of uncertainty in the predicted performance where results were reported to be reliable. The study revealed that the system achieved maximum performance when the rim angle was 68 o .…”
Section: Aamentioning
confidence: 99%
“…Similarly, Odeh et al (1998) used direct steam generation over an indirect steam generation in a PTC system and the system performance was calculated with the help of an equation. Agagna et al (2018) predicted the accuracy and performance of the system by comparing their PTC model with an existing system while the results reported about 0.5% of uncertainty in the predicted performance where results were reported to be reliable. The study revealed that the system achieved maximum performance when the rim angle was 68 o .…”
Section: Aamentioning
confidence: 99%
“…Maximum exergetic efficiency was recorded for liquid sodium. Agagna et al 17 proposed a user‐defined function built in a finite volume model to minimize the need to use a tracing model to investigate the thermal performance of a parabolic trough collector with a circular receiver. The results from the proposed model were validated with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various parameters on the thermal performance of the PTSC has been studied such as solar radiation, heat transfer fluid (HTF), mass flow rates and fluid inlet temperature 15,23 . Agagna et al 39 provided an improved model for analysing the thermal efficiency of PTSC. Some researchers also investigated the performance of large aperture PTSC 35,40‐44 .…”
Section: Introductionmentioning
confidence: 99%